The biological effect of orange (Citrus sinensis L.) by-products on metabolic biomarkers: A systematic review - Pineda-Lozano, Jessica Elizabeth; Fonseca-Bustos, Verónica; Martinez-Moreno, Alma Gabriela; Virgen-Carrillo, Carmen Alejandrina (Frontiers in Sustainable Food Systems, 2022)
Industrial processing of citrus fruits generates an important amount of wastes that evoke environmental damage. Orange is the main citrus fruit consumed worldwide, and after its use, approximately more than a half of the fruit remains as by-products, which comprise important bioactive compounds useful for the development of promising nutraceuticals for the treatment of non-communicable diseases. This study aimed to gather scientific evidence about the biological effects of orange by-products using a systematic review. A total of 14 studies that were carried out in rodent models in the last 10 years were retrieved from PubMed and ScienceDirect databases. Studies that used another animal species, another type of citrus, or a combination of orange with other citrus were excluded. The risk of bias was assessed by using the SYRCLE RoB tool, and the results obtained are shown in an informative table, which showed that most of the studies used a pathological model of chronic diseases. We found that the peel is the most used agri-food by-product, and that it has the potential of reducing the levels of triglycerides, total cholesterol, glucose, and systolic blood pressure. However, to clinically assess these effects, these results need to be tested in future in humans. The included studies on the use of orange by-products strengthen the global sustainable food agenda. It is important to consider new research directions about the use of citrus fruit residues since it not only impacts the problem of its disposal but also provides solutions to eliminate the resulting contamination.